Formability study and forming path optimization in single-point incremental forming process - D. Azodi, H.; M. Dariani, B.; Sedaghat, H.; Mohammadi, H. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Incremental sheet metal forming is becoming a popular approach for forming intricate shapes especially for rapid prototyping and small batch production of sheet metals. In this work, the formability of Aluminium sheet metal in a single-point incremental forming (SPIF) has been investigated numerically and the effect of the feed rate, the vertical feed (pitch) and the spindle revolution on the formability have been studied. Parameters study results built a base for enhancing SPIF process and presenting two approaches to optimize forming path. In these approaches, variation of vertical pitch has been considered and the effects of this parameter on the strain distribution and formability have been studied. It is found that these methods normalize the strain distribution and improve the formability. Finite element method (FEM) with the aid of design of experiments (DOE) technique is used for predicting the parameters effects and optimizing forming path. Experiments are also carried out to verify the validity of numerical results.